Pathomechanism of oxidative stress in cardiovascular-renal remodeling and therapeutic strategies - Verdiana Ravarotto; Giovanni Bertoldi; Lucia Federica Stefanelli; Federico Nalesso; Lorenzo A. Calò (The Korean Society of Nephrology, 2022)
The high prevalence of cardiovascular disease in patients with chronic kidney disease indicates significant interactions between pathogenic pathways operating in the kidney and heart. These interactions involve all cell types (endothelial cells, smooth muscle cells, macrophages, and others), components of the vasculature, glomeruli, and heart that are susceptible to oxidative damage and structural alterations. A vicious cycle occurs whereby harmful factors such as reactive oxygen species and inflammation damage of vascular structures that themselves become sources of additional dangerous/toxic components released into the local environment. The evidence of this vicious cycle in chronic kidney disease should therefore lead to add other factors to both traditional and nontraditional risk factors. This review will examine the processes occurring during progressive kidney dysfunction with regard to vascular injury, renal remodeling, cardiac hypertrophy, and the transversal role of oxidative stress in the development of these complications.